ChemInform Abstract: Base‐Free Chemoselective Transfer Hydrogenation of Nitroarenes to Anilines with Formic Acid as Hydrogen Source by a Reusable Heterogeneous Pd/ZrP Catalyst. Issue 9 (March 2015) - Tuteja, Jaya; Nishimura, Shun; Ebitani, Kohki
Abstract The catalyst is recovered and reused in three additional cycles without loss of its activity.